PEMBERDAYAAN PETANI SAWAH MELALUI KEGIATAN PEMBINAAN DAN PENDAMPINGAN DI KABUPATEN MAROS - Abdul Halim (Jurnal Pallangga Praja (JPP), 2020)
The research objective was to analyze the empowerment of rice farmers through coaching and mentoring activities in Maros Regency. This type of research is quantitative research, with the main instrument being a questionnaire. The research respondents were 380 rice field farmers who were taken using stratified random sampling technique. The data obtained, tabulated and grouped for the purposes of data processing and analysis. Empowerment of paddy farmers is analyzed based on the four development approaches, namely human development, business development, environmental development, and institutional development. The results showed the empowerment of rice farmers in Maros Regency, namely human development through education and training as well as counseling and mentoring; environmental development through guidance and assistance in the control of environmentally friendly pests, as well as business development through coaching and assistance in the application of production technology applications, while business development through guidance and assistance in processing and marketing of products, and institutional development through guidance and assistance in the strengthening of farmer groups has not been going well. For this reason, policies are needed that support the empowerment of rice farmers, especially in the processing and marketing of products and strengthening farmer groups.